Emerging 2D Organic-Inorganic Heterojunctions - Ke Pei; Tianyou Zhai (Cell Reports Physical Science, 2020)
Summary: The unique properties of two-dimensional (2D) materials have boosted intensive interests in combining distinct 2D materials into van der Waals heterojunctions for novel device structures. The organic-inorganic heterojunctions, integrating atomically thin inorganic materials with an unlimited variety of organic molecules, provide an ideal platform for broader, superior, and on-demand functional applications by incorporating customized organic molecules that particularly exhibit decent optoelectronic properties, promising scalability and remarkable flexibility. In this Review, emerging 2D organic-inorganic heterojunctions from the perspectives of materials, manufacturing, structures, and interfaces, as well as recent progress in functional applications, are provided. Two prototypical construction approaches are summarized—epitaxy growth and molecular doping—followed by four directions of device applications, including electronic device, optoelectronic device, energy harvesting device, and memory and neuromorphic device. Finally, the frontier challenges and future outlook associated with the organic-inorganic heterojunctions are highlighted, which is critical for the further development of this cross-fertilized research field.